Fractional growth conjecture: interregional financing spillovers and economic growth - Yuni Utami; Mohammad Arridho Nur Amin; Catur Wahyudi; Agus Prasetyono (Journal of Innovation in Business and Economics, 2025)
The purpose of this study is to explore the existence of interregional credit spillover effects on the economy of East Java. In addition, this study introduces the concept of fractional growth conjecture. Using a Vector Error Correction Model (VECM), the analysis is based on quarterly data for the period 2011:Q1–2020:Q4, covering East Java’s economic growth and bank credit distribution in East Java, Jakarta, Central Java, and West Java. Based on the VECM estimates, along with shock simulation, impulse response, and variance decomposition analyses, the results show that domestic bank credit plays a significant role in East Java’s economy. The spillover effect of credit growth from Jakarta tends to be positive in the short term but negative in the long term. Credit spillovers from Central Java show a negative impact in both the short and long term. Meanwhile, spillovers from West Java have a positive impact in both the short and long term. These findings also suggest the presence of fractional growth between East Java and Central Java. The existence of fractional growth is concerning because it implies that economic growth in one region may suppress growth in another, ultimately limiting the potential to drive optimal national growth.